Study on the different effects of aluminum doping on Fe-Mn and Ni-Mn based compounds as cathode material for sodium-ion batteries - Qiao, Danlei; Zhang, Yixuan; Su, Chang; Liu, Guoqiang; Wang, Qingxiang; Wen, Lei (Journal of industrial and engineering chemistry (Seoul, Korea), 2023)
Al-doped Fe-Mn and Ni-Mn based materials with P2-type layered structure has been synthesized and tested as a positive electrode material for rechargeable sodium batteries. The modification mechanisms of Al doping in Fe-Mn and Ni-Mn based materials have been discussed. The synthesized Al-doped Ni-Mn based material Na0.67Mn0.8Ni0.16Al0.04O2 delivers a reversible capacity of 135.1 mAh g−1, which corresponds to 92.1% of the initial capacity with excellent cyclability for 200 cycles. What’s more, it can still remain a capacity of 96.2 mAh g−1 at a current density of 2000 mA g−1. When the voltage range increase to 1.5 – 4.3 V, its initial discharge capacity can reach 190.3 mAh g−1.